(untitled) (Italian Review of Legal History, 2021)
Author explains that the importance of notaries in social urban live largely exceeded their percentage in urban population, normally assessed at 4% of cities’ population. Notaries’ social weight was due to their necessary and outstanding participation in written records of every kind, public as private. To reach notarial profession was the top of a social climbing that urban families, mostly belonging to craftsmanship, wished to attain. To such an attainment mastery of latin written language was unavoidable. From this basic knowledge notaries could raise and reach high levels of literary production, as author largely illustrates.